2014
DOI: 10.2478/jomb-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary-Gonadal, Pituitary-Adrenocortical Hormones and IL-6 Levels Following Long-Term Magnesium Supplementation in Male Students

Abstract: SummaryBackground: Sleep deprivation, malnutrition and lack of physical activity are contemporary stress-related factors present in the student population. Stress activates the HPA and often suppresses the HPG axis, but also influences cytokine synthesis and consequently regulates immune response. Since magnesium deficiency facilitates negative pathophysiological consequences, a reasonable question imposes, wheth er Mg supplementation might correct the adrenal/gon adal hormone balance and immuno-endocrine func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…Our results for rugby players before Mg supplementation corroborate these findings. One of our previous trials on a male student population showed that chronic magnesium supplementation caused decrease in serum cortisol level that was also accompanied by reduction in IL-6 level ( 25 ). There is a substantial amount of data pointing to the role of Mg in cytokine production as a part of HPA axis disturbance and/or immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Our results for rugby players before Mg supplementation corroborate these findings. One of our previous trials on a male student population showed that chronic magnesium supplementation caused decrease in serum cortisol level that was also accompanied by reduction in IL-6 level ( 25 ). There is a substantial amount of data pointing to the role of Mg in cytokine production as a part of HPA axis disturbance and/or immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind, randomized trial of 46 healthy adults aged 60–75 years, magnesium supplementation (magnesium 500 mg per day administered as magnesium oxide tablets for 8 weeks) improved subjective measures of insomnia, which is recognized as a symptom of stress [8, 9]. Magnesium supplementation over a period of one month (magnesium 500 mg per day in a magnesium oxide tablet) has also been shown to significantly decrease basal serum cortisol concentrations, a biomarker of stress, in students [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hirsch’s so-called H index was proposed as an alternative to other bibliometric indicators - such as the number of publications, the average number of citations and the sum of all citations ( 97 ) - and is defined as follows: “A scientist has index h if h of his or her Np papers have at least h citations each and the other (Np - h) papers have ≤ h citations each” ( 102 ). All papers by a scientist that have at least h citations are called the “Hirsch core” ( 13 ). An H-index of 5 means that a scientist has published five papers that each have at least five citations ( 97 ).…”
Section: Discussionmentioning
confidence: 99%